Comparing teachers’ aspiration towards change in teaching and learning and their actual classroom practices - Ismail, Habsah; Hassan, Roshafiza; Konting, Mohd Majid; Wan Ali, Wan Zah (Universiti Putra Malaysia Press, 2012)
This paper reports the findings of a study on teachers’ aspiration towards change in their teaching and learning and their actual practices in the classroom in the Malaysian Secondary Schools. An instrument consisting of 24 items was used to measure the perception of the teachers on the aspiration and the actual implementation towards teaching and learning in the classrooms of these schools. Findings of the study indicate that the mean score of their actual teaching practices is 3.88 and a standard deviation of 0.52, which is higher as compared to the score on the teachers’ aspiration towards change in teaching and learning, which obtained a mean of 3.13 and a standard deviation of 0.85. This study also reported that there are significant differences between the teachers’ aspiration towards change and their actual classroom practices based on gender, age, ethnic, professional qualification and types of school. Despite these differences, the general attitude of the teachers in this study was found to be rather positive towards their teaching and learning practices in the classrooms.